2012
DOI: 10.4236/ajps.2012.310176
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Newly Developed Wheat/Barley Introgression Lines in Respect of Aluminium Tolerance

Abstract: The Al tolerance of newly developed wheat/barley disomic addition, substitution and translocation lines carry chromosomes of three different barley cultivars was evaluated by comparing the root growth in solution containing 75 μM AlCl 3 at pH 4.0 to that of known Al-tolerant and sensitive wheat genotypes. The wheat Asakaze komugi, barley Manas cultivars and their hybrid derivatives were found to have high levels of Al tolerance. The wheat line Mv9kr1, barley cultivar Igri and progenies of the hybrids were sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…On such type of soil average concentrations of total Al varies typically between 42 mg/kg in the 0-30 cm soil layer to 21 mg/kg in the 125-170 cm layer (Altermann et al 2005). Solubility of Al in the soil arouses as a problem for plant growth at pH below 5 (Darkó et al 2012). Therefore, under the present conditions, the toxicity of Al was not an issue.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…On such type of soil average concentrations of total Al varies typically between 42 mg/kg in the 0-30 cm soil layer to 21 mg/kg in the 125-170 cm layer (Altermann et al 2005). Solubility of Al in the soil arouses as a problem for plant growth at pH below 5 (Darkó et al 2012). Therefore, under the present conditions, the toxicity of Al was not an issue.…”
Section: Methodsmentioning
confidence: 79%
“…At soil solution with pH > 6, Al is present in the form of an anion Al(OH) 4 but its phytotoxic features were not studied in detail (Ma et al 2003). Since small grains are very important crops, a lot of research has been done with the aim to understand and alter mechanisms of tolerance towards high concentrations of Al and the results show that significant differences exist between different genotypes (Tang et al 2002, Darkó et al 2012.…”
mentioning
confidence: 99%
“…Manas is a winter barley cultivar with good winter hardiness making it better adapted to Central European climatic conditions than Betzes. It also has favourable agronomic traits, including good yielding ability [ 9 ] and better salt and aluminium tolerance than the other two barley genotypes previously used to develop addition lines [ 28 30 ]. Wheat-alien ditelosomic additions have also been developed using other cultivated and wild relatives of wheat, including various cultivars of rye, Aegilops species, Thinopyrum ponticum , Elymus species, Leymus racemosus and Hordeum chilense .…”
Section: Discussionmentioning
confidence: 99%
“…Introgression lines are useful for investigating heterologous expression of genes from alien chromosomes in the wheat genetic background [ 56 ]. In previous experiments several wheat/barley addition and translocation lines carrying chromosomes from different wheat and barley cultivars were studied for aluminium and salt tolerance [ 29 , 30 ]. A comparison of the salt stress responses of Asakaze/Manas wheat–barley disomic addition lines (2H, 3H, 3HS, 4H, 6H, 7H and 7HL) to those of the parental genotypes (Asakaze, Chinese Spring and Manas) revealed that the disomic addition line 7H and the ditelosomic line 7HL exhibited higher salt tolerance both during germination and in the early developmental stages than the wheat parents, among which Asakaze had higher salt tolerance than Chinese Spring [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity of common wheat ( Triticum aestivum L.) can be extended via interspecific hybridization. One of the promising crossing partners is barley ( Hordeum vulgare L.), which has many agronomically useful traits, such as earliness [ 1 ], tolerance of biotic [ 2 , 3 ] and abiotic (Al and salt) stress [ 4 7 ], good tillering ability [ 8 , 9 ] and high grain protein [ 10 ] and dietary fiber content [ 11 , 12 ], which it would be desirable to transfer into wheat.…”
Section: Introductionmentioning
confidence: 99%